La bande dessinée pour construire une mémoire des « mille jours » de l’Unité populaire au Chili - Elsa Marsande (Cahiers d’histoire.)
The richness of the comic book format makes it possible to portray Chile from 1971 to 1973, from the implementation to the failure of the project led by Salvador Allende. It shows that the coup did not come by surprise: attacks, strikes and scandals were imposed in response to the implementation of the Popular Unity program. The political and social flourishing that emerges from this moment, the multiple reconfigurations and tensions that settle there, are restored in a historical fresco of exemplary precision.